Instilling Spiritual Awareness in Early Childhood: An Interpretative Phenomenological Analysis Study - Erwan Efendi (Journal of Health and Multidisciplinary Health Studies, 2026)
This study aims to explore the deep, lived experiences of early childhood educators and parents in instilling spiritual awareness in early childhood. While early childhood education heavily emphasizes cognitive and physical milestones, the subtle dimensions of spiritual consciousness are often under-researched and peripherally implemented. Employing an Interpretative Phenomenological Analysis (IPA) framework, this qualitative study investigated the psychological realities, meanings, and practical dynamics experienced by five educators and parents in Tulungagung, Indonesia. Data were gathered through semi-structured, in-depth interviews and analyzed via the iterative process of IPA, including initial noting, emergent theme development, and cross-case clustering. The analysis revealed three major master themes: (1) The structural integration of daily ritualistic routines as a foundational spiritual scaffold, (2) The absolute necessity of adult role-modeling within the child's immediate ecosystem, and (3) The systemic challenges arising from the polarization between modern materialistic educational orientations and internal spiritual growth. The findings indicate that spiritual awareness is not an abstract cognitive transfer but an experiential process catalyzed by the relational alignment of the adult ecosystem. This research underscores the need for a holistic educational paradigm shift that incorporates subjective spiritual experiences into formal early childhood curricula.